2016
DOI: 10.4102/hsag.v21i0.945
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' perceptions of their premature infant's communication: A description of two cases

Abstract: Qualitative a b s t r a c tBackground: Survival rates of premature infants have increased due to advances in medi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Maternal perceptions of a sleepy or unresponsive infant (Kritzinger & Louw, 2003;Nicolaou et al, 2009;Pascoe et al, 2016;Tanner, 2012): These reported perceptions lead to a feeling of onesided interaction and uncertainty on the mother's part (Pascoe et al, 2016).…”
Section: Thematic Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal perceptions of a sleepy or unresponsive infant (Kritzinger & Louw, 2003;Nicolaou et al, 2009;Pascoe et al, 2016;Tanner, 2012): These reported perceptions lead to a feeling of onesided interaction and uncertainty on the mother's part (Pascoe et al, 2016).…”
Section: Thematic Analysis Resultsmentioning
confidence: 99%
“…Kangaroo mother care (KMC) improves maternal perceptions of their preterm babies' early communication capabilities (Feldman, Eidelman, Sirota, & Weller, 2002;Flacking et al, 2006;Green & Phipps, 2015;Kritzinger & Louw, 2003;Kritzinger & Van Rooyen, 2014;McInroy & Kritzinger, 2005;Pascoe et al, 2016): A significant number (i.e. seven) of the included studies indicated that mothers who practiced KMC demonstrated a strong awareness of their role in early communication and the development thereof.…”
Section: Thematic Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing childhood development can be seen as either ‘risk’ or ‘protective’ in nature, as illustrated by Pascoe, Bissessur and Mayers’s ( 2016 ) application of the transactional model on childhood development. Furthermore, risk or protective influences on infant development and well-being can be viewed as existing within different levels of influence, such as those systems described by Bronfenbrenner’s ( 1989 ) bio-ecological model (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the study was to describe the above-described mothers’ experiences with regards to having, caring for and feeding their preterm infants (birth to 6 months of age) within low socio-economic circumstances. The study adopted a theoretical approach that reflected a combination of Bronfenbrenner’s bio-ecological systems model of childhood development ( Figure 1 ; Bronfenbrenner 1989 ) as well as the transactional model (Sameroff 2009 ) applied to childhood development (Pascoe et al 2016 ). Thus, this study explored ‘protective’ and ‘risk’ factors acting at different systems of influence that may affect childhood well-being and development through the experience of the mother.…”
Section: Introductionmentioning
confidence: 99%